2010
DOI: 10.1523/jneurosci.2023-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging Reveals the Neural Substrates of Arm Transport and Grip Formation in Reach-to-Grasp Actions in Humans

Abstract: Picking up a cup requires transporting the arm to the cup (transport component) and preshaping the hand appropriately to grasp the handle (grip component). Here, we used functional magnetic resonance imaging to examine the human neural substrates of the transport component and its relationship with the grip component. Participants were shown three-dimensional objects placed either at a near location, adjacent to the hand, or at a far location, within reach but not adjacent to the hand. Participants performed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
256
4
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 288 publications
(295 citation statements)
references
References 87 publications
(102 reference statements)
33
256
4
2
Order By: Relevance
“…The spatial aspect is crucial since it has been demonstrated that SPOC activity is strictly related to the transport component of the reach‐to‐grasp action (Cavina‐Pratesi et al. 2010). In contrast, our results are consistent with the study of Fabbri et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The spatial aspect is crucial since it has been demonstrated that SPOC activity is strictly related to the transport component of the reach‐to‐grasp action (Cavina‐Pratesi et al. 2010). In contrast, our results are consistent with the study of Fabbri et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2010). These authors reported that the human SPOC showed stronger activation during reach‐to‐grasp action toward far rather than near locations, suggesting a preference for the transport rather than the grasp component.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous other studies have confirmed Jeannerod's (1984) division of prehension into two distinct and separable components (Dohl, Ostermann, Hefter & Freund, 2000;Shallice, Venable & Rumiati, 2005) with some authors demonstrating that these, furthermore, have distinct neural substrates (e.g. Cavina-Pratesi et al 2010).…”
Section: Introductionmentioning
confidence: 85%
“…It has been proposed that inside the dorsal stream there may be diverse circuits mediating different components of movement control [22][23][24] .…”
Section: Introductionmentioning
confidence: 99%